The genus Dolichocephala newly found in Shaanxi Province (China), with descriptions of three new species (Diptera: Empididae) - Liu, Xiaoyan; Wang, Mengqing; Yang, Ding (Zootaxa, 2014)
The genus Dolichocephala is recorded from Shaanxi Province (China) for the first time. The following three new species are described: Dolichocephala brevis sp. nov., D. longa sp. nov., and D. qinlingensis sp. nov. Their relationships with related species are discussed. An updated key to the species of Dolichocephala from China is presented.